Implemantation Of Audit Procedures For Cash And Cash Equivalent Accounts Of T Foundation By KAP Djoko Soerjadi - Kartika Retnaningrum; Sri Trisnaningsih (International Journal of Economics and Management Sciences, 2025)
Cash is a crucial asset in a company and is often a prime target for fraud. Therefore, it is necessary to conduct a rigorous financial examination of cash equivalents to ensure that an entity's cash balance has been recorded correctly. T Foundation is a non-profit educational foundation that relies on cash in financing its operational activities. This study was conducted to analyze the implementation of cash account audit procedures at the T Foundation carried out by KAP Djoko Soerjadi in accordance with general cash equivalent audit procedures. The research method used is descriptive qualitative. The results showed that what was done by KAP Djoko Soerjadi at the T Foundation on cash equivalents had complied with the established audit procedures. However, in the implementation process, auditors face several obstacles, such as the slow response from clients in providing data information needs and complementary documents, which results in hampering the audit process so that the work takes longer than expected.